2021
DOI: 10.1186/s12960-021-00621-z
|View full text |Cite
|
Sign up to set email alerts
|

Public availability of information from WFME-recognized accreditation agencies

Abstract: The World Federation for Medical Education (WFME) Recognition Programme was created to ensure the comparability of medical school accrediting agencies, so that the schools accredited by those agencies would have similar educational quality. WFME explicitly values transparency and has recognition criteria that relate to agencies making information publicly available. Our study examined 20 WFME-recognized agencies’ transparency by reviewing agency websites for 27 information elements related to accreditation sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…Results of the study showed the relatively unsatisfactory overall status of public availability of information from medical schools in China. The finding is consistent with Baniadam and colleagues’ study of 20 WFME-recognized agencies’ transparency, which revealed that while 12 agencies had over 90% of expected information elements related to accreditation standards, procedures, and processes available on agency websites, 6 agencies had less than 50% information elements accessible [ 12 ]. They indicated that some WFME-recognized agencies present significant barriers for stakeholders of accreditation due to a lack of transparency [ 12 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Results of the study showed the relatively unsatisfactory overall status of public availability of information from medical schools in China. The finding is consistent with Baniadam and colleagues’ study of 20 WFME-recognized agencies’ transparency, which revealed that while 12 agencies had over 90% of expected information elements related to accreditation standards, procedures, and processes available on agency websites, 6 agencies had less than 50% information elements accessible [ 12 ]. They indicated that some WFME-recognized agencies present significant barriers for stakeholders of accreditation due to a lack of transparency [ 12 ].…”
Section: Discussionsupporting
confidence: 86%
“…The finding is consistent with Baniadam and colleagues’ study of 20 WFME-recognized agencies’ transparency, which revealed that while 12 agencies had over 90% of expected information elements related to accreditation standards, procedures, and processes available on agency websites, 6 agencies had less than 50% information elements accessible [ 12 ]. They indicated that some WFME-recognized agencies present significant barriers for stakeholders of accreditation due to a lack of transparency [ 12 ]. Our result echoed Verkijika and De Wet’s finding in their accessibility evaluation of all 26 South African university websites that none of the websites met all the WCAG (Web Content Accessibility Guidelines) 2.0 accessibility criteria [ 18 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although accreditation protocols are often not publicly accessible [ 12 ], we searched accrediting organizations’ websites for documents describing their protocol. If that failed, we attempted to obtain the documents by contacting the organization and emailing our professional networks.…”
Section: Methodsmentioning
confidence: 99%
“…Two related issues touched on in these articles could benefit from further exploration, including accreditation's role in increasing public availability of information and how quality assurance information is used, or not used, to evaluate institutions for the purpose of gatekeeping of international medical graduates (IMGs) throughout the world. Many accreditation systems and the WFME Recognition Program strive, albeit with some limited success, [5][6][7] to increase the amount and public availability of information on educational institutions so students can make informed choices. Just as the United States is only one of two countries (the other being New Zealand) that allow pharmaceutical companies to advertise regulated drugs directly to consumers, the medical education field in this country is encumbered by commercials for educational institutions with potentially misleading or incomplete information on the quality of education delivered, student success, and practice opportunities for physician graduates.…”
mentioning
confidence: 99%